PENINGKATAN KEMAMPUAN MENULIS BAHASA INDONESIA MELALUI PENERAPAN DIRECTED WRITING ACTIVITIES PADA SISWA KELAS X-4 SMA NEGERI 1 MANDAI MAROS - Santiung, Welly (Jurnal Ilmiah Administrasita, 2014)
Purpose of this research to measure ability influence writes student through applying of Directed Writing Activities in supporting attainment result of learning Indonesian language class student X-4 SMA NEGERI 1 Mandai Maros, South of Sulawesi school year 2009/2010. Population of Research is all class student X-4 SMA in school year 2009/2010. Sampling method applied is Cluster Random. Medium of data collecting technique is done by using test. Observation in this case is ability writes student, medium of test in this case is test result of student learning. To process data applies descriptive statistic technique, by using frequency distribution and mean percentage, and deviation standard, to see ability writes student in supporting attainment result of learning Indonesian language class student X-4 SMA NEGERI 1 Mandai Maros South of Sulawesi. Research result obtained by ability to write class student X-4 SMA NEGERI 1 Mandai Maros South of Sulawesi in general stays in low category at cycle I with score average of 54,25 and deviation standard 15,31 while at cycle II increases to become 69,63and deviation standard 13,84